Determinasi Profitabilitas Pada Industri Pertanian: Tinjauan Atas Pengaruh Biaya Operasional dan Debt To Assets Ratio - Nurjanah, Dara Siti; Munawar, Andri Helmi; Hadiani, Dian; Melanie, Arin; Pratama, Reza (Program Studi Perbankan dan Keuangan Fakultas Ekonomi Universitas Siliwangi, 2025)
This study aims to answer whether operating costs, proxied by the operating expense ratio (BOPO), and the Debt to Assets Ratio (DAR) affect the profitability of agricultural sector companies, as measured by Return on Assets (ROA), both partially and simultaneously. The research employs a quantitative descriptive–verificative approach using secondary data from the annual financial statements of eight agricultural firms listed on the Indonesia Stock Exchange (IDX) for the period 2020–2022, yielding 24 firm-year observations. Samples were selected through purposive sampling. Data were analyzed using multiple linear regression with SPSS version 25, preceded by classical assumption tests including normality, linearity, multicollinearity, heteroscedasticity, and autocorrelation. The empirical results show that BOPO and DAR jointly have a significant effect on ROA, whereas individually neither BOPO nor DAR exhibits a statistically significant effect at the 5% level. The coefficient of determination (R²) of 27.2% indicates that the combination of BOPO and DAR explains only a portion of the variation in profitability, while the remaining variation is driven by other factors outside the model. These findings imply that, in the agricultural industry, cost efficiency and capital structure remain relevant, but they are not sufficient as standalone bases for managerial or investment decisions without considering additional internal and external determinants.Keywords: operating costs, Debt to Assets Ratio, Return On Asset.